2017
DOI: 10.1016/j.foodchem.2017.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pan cooking on micropollutants in meat

Abstract: This work presents the effects of pan cooking on PCBs, PCDD/Fs, pesticides and trace elements in meat from a risk assessment perspective. Three different realistic cooking intensities were studied. A GC×GC-TOF/MS method was set up for the multiresidue analysis of 189 PCBs, 17 PCDD/Fs and 16 pesticides whereas Cd, As, Pb and Hg were assayed by ICP-MS. In terms of quantity, average PCB losses after cooking were 18±5% for rare, 30±3% for medium, and 48±2% for well-done meat. In contrast, average PCDD/F losses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
0
13
0
3
Order By: Relevance
“…Planche et al. () investigated the effects of pan cooking on PCBs, PCDD/Fs and other contaminants in meat. The average PCB losses after cooking were 18±5 % for rare, 30±3 % for medium, and 48±2% for well‐done meat.…”
Section: Assessmentmentioning
confidence: 99%
“…Planche et al. () investigated the effects of pan cooking on PCBs, PCDD/Fs and other contaminants in meat. The average PCB losses after cooking were 18±5 % for rare, 30±3 % for medium, and 48±2% for well‐done meat.…”
Section: Assessmentmentioning
confidence: 99%
“…A study by Wells et al demonstrated the advantages of GC × GC coupled with TOF−MS that enabled simultaneous detection of 206 contaminants in beef and fish samples, including 189 PCBs and 17 PCDD/Fs. 44 Current research efforts have also been made to investigate new POPs under the Stockholm Convention, such as decabromodiphenyl ether (DBDE), octabromodiphenylether (octaBDE), hexabromobiphenyl (HBB), hexachlorobutadiene (HCBD), pentachlorobenzene (PeCB), hexabromodiphenyl ether (hexaBDE), perfluorooctanesulfonic acid (PFOS), and perfluorooctanoic acid (PFOA). These chemicals were used as flame retardants or industrial additives that may be present in packing materials and contaminated foods.…”
Section: Analysis Of Endogenous and Exogenousmentioning
confidence: 99%
“…Indeed, the past ten years have seen a number of very interesting studies based on modeling and on emerging analytical approaches (analytical chemistry, toxicogenomics, etc. ), particularly in the field of chemical safety for meat products [64][65][66][67][68][69][70]. These studies focused on the whole meat chain, from livestock exposure to micropollutants during farming [67] to meat digestion in the human gut [68,71].…”
Section: Example Of the Meat Sectormentioning
confidence: 99%
“…These studies focused on the whole meat chain, from livestock exposure to micropollutants during farming [67] to meat digestion in the human gut [68,71]. In terms of processes applied to meat, several papers have demonstrated the relevance of combining analytical techniques, such as multi-dimensional gas chromatography, olfactometry, and mass spectrometry, to investigate both the heat-induced toxicants and odor-active compounds formed when cooking meat [69,70].…”
Section: Example Of the Meat Sectormentioning
confidence: 99%